The letter instance in the reading - Milmann, Elaine (Clinical Styles. The Journal on the vicissitudes of childhood, 2003)
The letter instance in the reading mentions the overflow to it for the psychotic subjective act in the text. The work is developed from the psychopedagogical clinic experience with a interdisciplinar team and a school, considering a dialogue between psychoanalysis and education. Following some reading situations, one hypothesis appears: with the reading acts, it is possible to point out the singularity of the psychotic subjectivity in its relations with the meaning. This could be analyzed from the point of view of listening of the language phenomena that appear when the reader speaks about the read text. Also it would be possible to certify the letter incidence in the developing of the "Borromeano" enlancing, the three registers, RSI. Attempting to demonstrate the singularity of the relation between psychosis and the meaning field, reading situations lived by a boy with this diagnosis are presented and the material gathered is analyzed from the readings.